Faktor Risiko Hasil Janin/Bayi pada Wanita Hamil dengan Kanker di Jawa Timur Indonesia: Studi Epidemiologi - Nardeen Adel Mekhail Naoum; Ernawati Darmawan (Universitas Airlangga, 2023)
Background: Cancer during pregnancy is a rare event, despite its rarity, its incidence nowadays keeps on increasing worldwide. Objective: This study aims to describe the available data on pregnant women with cancer in East Java- Indonesia, maternal outcomes and fetal outcomes, and knowing the risk factors of bad fetal outcomes in pregnant women with cancer from an epidemiological point of view. Method: This is a quantitative observational study of pregnant women with cancer in East Java Indonesia. Its design is a Cross-sectional study. Data collection was obtained from secondary data (the medical report in the Obgyn department at Dr. Seotomo Hospital from 2016 – 2020). Data were analyzed statistically by using SPSS program version 25. Result: The results showed that from 2016 to 2020, 54 cases of pregnant women with cancer had been extracted with an incident rate 0.8%. The incident rate of Non-Obgyn Cancer (55.6%) is higher than Obgyn Cancer (44.4%). The highest incident rates in non-Obgyn Cancer are Breast cancer (7.5%) and Leukemia (3.7%), while the highest incident rates in Obgyn Cancer are Cervical and Ovarian (8.4%). There was no relationship between cancer type and fetal outcomes, while there is a relationship between cancer stage and fetal outcomes. Conclusion: Cancer stage could be risk factor for fetal outcomes in Indonesian pregnant women with cancer.